Gender differences in managers' attitudes toward depressed employees: a cross-sectional study. (13th November 2019) - Mangerini, I; Bertilsson, M; de Rijk, A E; Hensing, G
Abstract: Background: Depression is known to carry negative attitudes within society and organisations. In the workplace, managers are responsible for the psycho-social work environment and attitudes to depression will likely affect that environment. The few studies performed among managers have found that female, more educated and managers working in the public sector were less likely to report negative attitudes. However, these studies did not take organization characteristics into account. The aim was to investigate the association between gender and negative attitudes toward employees with depression controlling for individual and organisational factors. Methods: A cross-sectional web-survey was sent to 4737 Swedish managers, aged 20-65 years in 2017, response rate 71%; We included those answering the "Managerial stigma toward employee depression" instrument, n = 2663 (901 women, 1762 men), consisting of 12 items tapping negative attitudes towards depression. The 3rd quartile was used as a cut-off. Multivariate logistic regression analyses on attitudes towards depression were performed (95% CI) to generate odds ratios (OR) adjusted for co-variates (individual and organisational characteristics). Results: Male managers were more likely to report negative attitudes compared to female managers (OR 1.64, 95% CI 1.28 - 2.10) irrelevant of individual (age, education, current workplace management experience, lifetime experience in management, managerial position) or organisational (work sector, staff gender composition, presence of staff members with Common Mental Disorders) characteristics. Conclusions: A gender difference in reporting negative attitudes was appraised regardless any of the co-variates included. To manage depression within the workplace, companies should also address managers' attitudes towards depression. Key messages: Important to heed managers' attitudes to CMDs and their impact on RTW processes. Gender-tailored approach in managers' training is suggested for awareness and knowledge on mental health.